Comorbidities of deformational plagiocephaly in infancy: a scoping review protocol - Mijna Hadders-Algra; Lia Charalambous; Edna N. Yamasaki; Sofia Lampropoulou (BMJ Publishing Group, 2021)
Introduction Deformational plagiocephaly (DP) is one of the most common cranial shape disorders in infancy. It is characterised by unilateral flattening of the skull due to head preference to one side. The literature suggests that DP is associated with comorbidities such as developmental delay, but the nature and prevalence of the comorbid impairments are still unclear and controversial. Therefore, our scoping review (ScR) aims to explore systematically the extent and nature of literature by identifying, mapping and categorising the most relevant comorbidities of DP in children up to the age of 2 years.Methods and analysis This protocol is based on the framework outlined by Arksey and O'Malley. A systematic search will be conducted to identify relevant full text studies from 1992 to 2021 using the databases of Cochrane, MEDLINE, Google Scholar, EMBASE, PubMed and University of Nicosia EBSCO. Two independent reviewers will screen abstracts and full articles in parallel, using specific inclusion and exclusion criteria. Specifically, this review will consider studies investigating DP and relevant comorbidities in children up to the age of 2 years of life without craniosynostosis, torticollis and any other diagnosed neurodevelopmental deficiency.The Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for ScR Checklist will be considered for results' analysis and reporting. The results will be described in a narrative form in relation to the research question and in the context of the overall study purpose.Ethics and dissemination Research ethics approval is not required for this ScR since data will be retrieved from publicly available studies. Dissemination activities will include research findings' submission for publication in a relevant peer-reviewed journal and presentation of the results at relevant conferences.Registration Our protocol was registered prospectively with the Open Science Framework (https://osf.io/48am3/).